Crop Production - Goyal, Aakash; Asif, Muhammad (IntechOpen, 2013)
Humans are depended on crops for food, fibber and more recently for fuel. Demands for crop production in rising because of increasing population, change in food habits and biofuel consumption. The book focus on challenges, progress and prospects of crop production. It comprises of vast array of topics including latest agronomics practices for different crops to enhance productivity, mitigate the challenges imposed by climate change, improve water use efficiency, factors controlling dormancy, optimum use of fertilizers etc. This volume will serve as an excellent resource for students and researchers interested and working in the area of sustainable crop production.